ChemInform Abstract: Quantum Criticality and Unconventional Order in Magnetic and Dielectric Material. Issue 47 (4th November 2013) - Rowley, S.; Smith, R.; Sutherland, M.; Alireza, P.; Saxena, S.; Lonzarich, G.
Abstract Review: 15 refs.